The Integrated Approach to Teaching Arabic Language Skills and Its OutputsThe integration situations for the intermediate education certificate examination(2015/2019) as a corpus. (مجلة إحالات, 2026)
There are many approachesin language education, with many theoretical efforts that have been invested in language, whether inside or outside the linguistics field. So it was the skilled approach, the communication approach, and the integrator approach.., Our study in its theoretical section dealt with the integrative approach in teaching Arabic language skills and its outputs, and on the practical side, we purposely reveal the characteristic of integration in the integrative situations (essays), and this in the Arabic language exam for intermediate education certificate between my year: 2015 and 2019 AD, and conducting a descriptive and analytical study onthese topics in line with the integrative approach. One of the most important results we have achieved is the necessity of an integrative evaluation of all Arabic language  skills: listening and speaking, reading and writing. If teaching Arabic language skills depends on the integrative approach; the assessment of their achievement, especiallyin the inclusive situation, must be built as well according to the requirements of this approach.